Identifikasi Isolat Mycobacterium bovis Dengan Konsentrasi Dna Bertingkat Menggunakan Teknik Polymerase Chain Reaction - Yohanes T. R. M. R. Simarmata (JURNAL KAJIAN VETERINER, 2019)
Mycobacterium sp. is a bacteria that can cause tuberculosis disease in domestic animals. Mycobacterium bovis pathogens in 3rdrisk groups and Indonesia as the country's fourth-largest contributor of Tuberculosis in the world after India, China and South Africa. Based on these facts, the research was conducted to identify M. bovis with DNA stage concentrations, hope of the lowest concentration can be used as a reference for the detection of tuberculosis.Isolate DNA samples obtained from the Center for Veterinary Research (BBalitvet) in Bogor, West Java. Dilution of the DNA was started from concentration 5000 pg / mL; 2500 pg / mL; 1250 pg / mL; 625 pg / mL; 312.5 pg / mL; 156.25 pg / mL; 78.125 pg / mL and 39.0625 pg / mL . DNA amplification by PCR using two pairs of primers JB21 and JB22 Forward INS1 Reverse and Forward and Reverse INS2 with predenaturasi conditions 94 ° C for 5 min, denaturation 94 ° C for 1 min, annealing 60 ° C for 1 min, 72 ° C elongation for 1 min and post-elongation 72 ° C for 7 min at 35 cycles. PCR reaction products of 500 bp and 245bp.Analysis results can be seen in the concentration of 78.125 pg / mL and 39, 0625 pg / mL with primary INS1/INS2, bands (bands) starts to look faded and disappeared. PCR using primers JB21/JB22 showed that the concentration 39.0625 pg / mL bands had disappeared. This can be done as a source of reference for the detection of Mycobacterium bovis infection.